2021
DOI: 10.3390/ijms222011230
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Germinosome Formation and FRET-Based Analysis of Interactions between GerD and Germinant Receptor Subunits in Bacillus cereus Spores

Abstract: Spores of the bacterium Bacillus cereus can cause disease in humans due to contamination of raw materials for food manufacturing. These dormant, resistant spores can survive for years in the environment, but can germinate and grow when their surroundings become suitable, and spore germination proteins play an important role in the decision to germinate. Since germinated spores have lost dormant spores’ extreme resistance, knowledge about the formation and function of germination proteins could be useful in sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…Considering initiation of spore nutrient germination, a recent study suggested that in B. subtilis, GerAB is responsible for sensing L-alanine, indicating that the function of GerA's B subunit is to detect nutrient germinants [27]. Our recent studies also suggest that there is interaction of GerRB with GerD and with a GR B subunit possibly bound by L-alanine [7,28].…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Considering initiation of spore nutrient germination, a recent study suggested that in B. subtilis, GerAB is responsible for sensing L-alanine, indicating that the function of GerA's B subunit is to detect nutrient germinants [27]. Our recent studies also suggest that there is interaction of GerRB with GerD and with a GR B subunit possibly bound by L-alanine [7,28].…”
Section: Discussionmentioning
confidence: 66%
“…The correct construction of recombinant plasmids pHT315-f14 and pHT315-f15 was confirmed by sequencing, followed by electroporation into competent B. cereus ATCC 14579 cells, and selection and confirmation with colony PCR of an erythromycin-positive single colony. PR-gerR(A-C-B)-SGFP2 [7] strain 007 +pHT315-f05 Ery r PD-gerD-mScarlet-I [7] strain 010 +pHT315-f10 Ery r PD-gerD-SGFP2 [7] strain F06 +pHT315-f06 Ery Abbreviations: PEa, promoter of spoVA operon; PR, promoter of gerR operon; PD, promoter of gerD; Ery r , resistant to erythromycin.…”
Section: Recombinant Plasmids and B Cereus Strainsmentioning
confidence: 99%
See 3 more Smart Citations